Nonnegative solutions of parabolic operators with low-order terms - L. Riahi (Electronic Journal of Qualitative Theory of Differential Equations, 2003)
We develop the harmonic analysis approach for parabolic operator with one order term in the parabolic Kato class on $C^{1,1}$-cylindrical domain $Ω$. We study the boundary behaviour of nonnegative solutions. Using these results, we prove the integral representation theorem and the existence of nontangential limits on the boundary of $Ω$ for nonnegative solutions. These results extend some first ones proved for less general parabolic operators.